THE INFLUENCE OF SEDIMENT BUDGET ON FLUID-RELATED DEFORMATION IN FOSSIL ACCRETIONARY PRISMS: A COMPARISON THE INTERNAL LIGURIAN UNITS (ITALY) AND THE FRANCISCAN COMPLEX (U.S.A). - Meneghini, Francesca; Marroni, Michele; Moore, James Casey; Pandolfi, Luca (Ofioliti, 2004)
The tectonic and deformation processes active during transfer of material in accretionary prisms are the results of a complex interplay of different factors. Among those, as demonstrated by studies on modern accretionary prisms, the mutual dependence between fluid circulation and sediment budget seems to play a crucial role in influencing the morphology and dynamics of both prisms and décollement zone.In this work we report a detailed structural study of two examples of fossil prisms characterized by different sediment budgets, and representative of different accretionary processes: the Franciscan Complex (FC, N-California) and the Internal Ligurian Units (ULI, N-Apennines). Two fluid circulation models are proposed and their comparison suggests that sediment budget controls prism hydrogeology and tectonics.The analyses of the two analogues have shown that, despite a different structural style, in both examples deformation is strongly controlled by repeated injection of overpressured fluids during underthrusting and accretion. Hydrofracturing occurs through dilatant fractures sub-parallel to the décollement zone, favored also by the wedge regional stress field. Fluid injection is transient, is associated with variation of local stress field at the décollement, and cyclical variation of permeability and cohesion states of rocks and sediments, allowing cyclical variation of deformation mechanisms and crosscutting veining episodes.The sediment budget at trenches controls the fluid pathways, which are located along the sedimentary layers of the turbiditic deposits in the ULI. Moreover, the presence of thick sequences of sediments, which undergo modification while moving to depth, allows the deformation to be strongly influenced by diagenetic processes. While deformation mechanisms, hydrofracturing and veining are essentially “shear zone (i.e. tectonically)-controlled” in the FC, in the ULI they are syn-diagenetic, and change when mechanical and diagenetic conditions in the turbiditic sequence, such as lithification state and competency contrasts, change.